Correlation between Covid-19 and weather/climate indicators: A Response - Ansari Saleh Ahmar (JINAV: Journal of Information and Visualization, 2020)
This is a response to article by Dr. Ramadhan Tosepu and his colleagues entitled: “Correlation between the weather and the Covid-19 pandemic in Jakarta, Indonesia” in Science of The Total Environment, Vol. 725; and Dr. Muhammad Farhan Bashir and his colleagues entitled: “Correlation between the climate indicators and the Covid-19 pandemics in New York, USA.” in Science of The Total Environment, Vol. 728. We agree with the results of their research, but there are things that need to be clarified in relation to the selection of the Spearman-rank correlation as an analytical tool, because the selection of this analysis is without the normality test of the data. Spearman-rank correlation is useful for non-normally distributed continuous data; can be used for ordinal data; and is relatively robust for outliers.